(untitled) (Journal of Parents and Teachers, 2014)
Starting from the premise that it is not necessary to be excessively original, but a wonderful narrator of stories, Fran Araújo reveals the elements to keep in mind when writing a script. Thus, the script, among other factors such as the choice of actors or the broadcast time slot, will make a television series a success or a failure.